Training general practitioners and medical assistants within the framework of HoPES3, a holistic care program for elderly patients to integrate spiritual needs, social activity, and self-care into disease management in primary care - Kunsmann-Leutiger, Elke; Straßner, Cornelia; Schalhorn, Friederike; Stolz, Regina; Stotz-Ingenlath, Gabriele; Buhlinger-Göpfarth, Nicola; Bentner, Martina; Joos, Stefanie; Valentini, Jan; Frick, Eckhard (Journal of multidisciplinary healthcare, 2021)
Training general practitioners and medical assistants within the framework of HoPES3, a holistic care program for elderly patients
Gesehen am 12.08.201